Achievement of highly conductive p-type transparent NdCuOS film with Cu deficiency and effective doping. (December 2018) - Zhang, N.; Liu, X.; Shi, D.; Tang, B.; Annadi, A.; Gong, H.
Abstract: Future advanced invisible or transparent electronics necessitate the need to overcome the well-known challenge in achieving high-performance p-type transparent semiconducting oxides (TSOs). Here, we report our success in achieving an outstanding p-type TSO thin film NdCuOS, which is the best performing p-type TSO reported to date based on the figure of merit (FoM) according to the best of our knowledge. In this work, we designed a novel chemical solution method to prepare the highly performing NdCuOS films with different doping elements. Our success in using a chemical solution method to grow semiconducting NdCuOS demonstrates that highly conductive oxychalcogenide films are possible to be prepared by a solution method. Such a solution method is facile, economically efficient, and scalable. Among our NdCuOS films with different dopants, we find that Mg-doped NdCuOS film demonstrates a very high p-type conductivity of 52.1 S cm −1 and optical transmittance of 54.3% with a huge FoM value of 1706 μS. This surpassed all the other p-type films reported so far in terms of FoM. Strong photoluminescence peaks at 3.0 eV are observed for our films, indicating their great potential applications for UV or blue light LED and other devices. The science behind such a successful achievement of high-performance p-type NdCuOS film is analyzed and discussed. A transparent p-n diode with very low leakage current (9.12 μA at −3 V) and turn-on voltage (1.1 V) is successfully fabricated, and it demonstrates a good device performance. Graphical abstract: A novel chemical solution method to prepare the highly performing NdCuOS films with the highest figure of merit (FoM) achieved so far and excellent device performances.